Análisis de la deuda externa y su relación con el producto interno bruto en la economía ecuatoriana - Vargas Montero, Jazmín Geanella (2023)
The increase in Ecuador's external debt has been affected by the lack of guidelines that correct the over-indebtedness towards the various projects that are managed by the Government of the day. It was also found that there is an increase in the ratio of external debt in relation to gross domestic product in the study period. The objective of this project was to analyze the behavior of the external debt and the gross domestic product of Ecuador and its multiple effects in the period 2007 - 2016. The methodology used in this research was a mixed approach, of a documentary and descriptive type, going to sources such as the ECB, Ministry of Economy and Finance, to find the data of the study period. Among the most important results of the research, the direct strong correlation that exists between the two variables under study stands out. The investigation led to a comparative analysis with all the periods studied to see the behavior of the debt and the gross domestic product, a Pearson correlation analysis was also carried out with the external debt and GDP variables to measure how correlated the variables are. The project carried out verified that risk management mechanisms must be implemented to identify and evaluate the risks associated with external debt, and thus take preventive and corrective measures to minimize their impact on public finances.